Evaluation of bacteriology of middle ear in early quiescent stage of chronic otitis media - Bhandari, Ramesh; Bhattarai, H; Pokhrel, BM (Journal of College of Medical Sciences-Nepal, 2013)
Objectives The objectives of this study were to determine whether any organism does exist in middle ear cavity during the early quiescent stage of chronic otitis media and to isolate their types. Materials and methods Forty-seven patients of age 13 years and above with diagnosis of chronic otitis media mucosal type in early quiescent stage were included. Swab was collected from middle ear cavity for culture and sensitivity in operation theatre prior to middle ear surgery and brought to microbiology laboratory within half an hour to inoculate in Blood agar, Chocolate agar and Mac Conkey agar. The isolates were identified with the use of standard bacteriological technique. Results Aerobic bacteria were isolated from 15 cases (31.9%). Staphylococcus aureus isolated in 12(80%), Pseudomonas aeruginosa in 2(13.3%) and E. coli in 1(6.7%). Conclusion Aerobic bacteria were isolated from middle ear cavity in quiescent stage of chronic otitis media in 15(32%) cases. Staphylococcus aureus was the most common organism. Journal of College of Medical Sciences-Nepal, 2012, Vol-8, No-4, 22-26 DOI: http://dx.doi.org/10.3126/jcmsn.v8i4.8696